Validity of The Guarantee Bond Agreement with Life Insurance Policy as The Object of Guarantee - Ni Made Kintan Ayu Arya Putri; I Made Dedy Priyanto (NOTARIIL Jurnal Kenotariatan, 2025)
This study examines the legal status of conventional life insurance policies as collateral objects in bank financing based on the Civil Code (KUHPerdata). The main focus lies on two issues: (1) whether life insurance policies can be categorized as intangible objects according to Article 511 paragraph (3) of the Civil Code; and (2) how is the validity of the collateral binding agreement for the life insurance policy. By using the normative legal research method through literature study, it was found that life insurance policies are conditional obligations whose validity depends on certain events (for example, the death of the insured). Therefore, this policy cannot be classified as an object within the meaning of Article 511 paragraph (3) of the Civil Code because it does not contain any achievements that can be directly collected. In addition, as an independent principal agreement, insurance policies cannot be used as primary collateral in credit agreements because they conflict with the principle of accessory agreements. Combining the function of the policy as primary collateral in one unit with a credit agreement has the potential to cause the agreement to be void by law. However, insurance policies can be used as additional collateral (second way out) as long as they maintain their basic function as risk coverage contracts. This research contributes to strengthening the legal framework of guarantees and providing legal certainty for financial institutions and customers in credit guarantee practices.